Thermodynamically Stable, Photoreversible Pharmacology in Neurons with One‐ and Two‐Photon Excitation. Issue 38 (23rd August 2018) - Passlick, Stefan; Richers, Matthew T.; Ellis‐Davies, Graham C. R.
Abstract: Photoswitchable bioprobes enable bidirectional control of cell physiology with different wavelengths of light. Many current photoswitches use cytotoxic UV light and are limited by the need for constant illumination owing to thermal relaxation in the dark. Now a photoswitchable tetrafluoroazobenzene(4FAB)‐based ion channel antagonist has been developed that can be efficiently isomerized in two separate optical channels with visible light. Importantly, the metastable cis configuration showed very high stability in the dark over the course of days at room temperature. In neurons, the 4FAB antagonist reversibly blocks voltage‐gated ion channels with violet and green light. Furthermore, photoswitching could also be achieved with two‐photon excitation yielding high spatial resolution. 4FAB probes have the potential to enable long‐term biological studies where both ON and OFF states can be maintained in the absence of irradiation. Abstract : The switcheroo : A photoswitchable quarternary ammonium probe with a long‐lived cis ‐isomer allows photopharmacological control of voltage‐gated ion channels in neurons that is stable in the dark. Isomerization is achieved using green and violet light and the switch shows two‐photon activity.